Reaction path models of magmatic gas scrubbing - DI NAPOLI, Rossella; AIUPPA, Alessandro; BERGSSON, Baldur; VALENZA, Mariano; Ilyinskaya, E; Pfeffer, M. A; Guðjónsdóttir, S. R (Chemical Geology, 2016)
Gas–water–rock reactions taking place within volcano-hosted hydrothermal systems scrub reactive, water-soluble species (sulfur, halogens) from themagmatic gas phase, and as such play amajor control on the composition of surface gasmanifestations. A number of quantitativemodels ofmagmatic gas scrubbing have been proposed in the past, but no systematic comparison ofmodel resultswith observations fromnatural systems has been carried out, to date. Here, we present the results of novel numerical simulations, in which we initialized models of hydrothermal gas–water–rock at conditions relevant to Icelandic volcanism. We focus on Iceland as an example of a “wet” volcanic region where scrubbing iswidespread.Our simulationswere performed (using the EQ3/6 software package) at shallow (temperature < 106 °C; low-Tmodel runs) and deep hydrothermal reservoir (200–250 °C; high-T model runs) conditions. During the simulations, a high-temperaturemagmatic gas phase was added stepwise to an initial meteoric water, in the presence of a dissolving aquifer rock. At each step, the chemical compositions of coexisting aqueous solution and gas phase were returned by the model. The model-derived aqueous solutions have compositions that describe the maturation path of hydrothermal fluids, from immature, acidic Mg-rich waters, toward Na–Cl-rich mature hydrothermal brines. The modeled compositions are in fair agreement withmeasured compositions of natural thermal waters and reservoir fluids from Iceland. We additionally show that the composition of the modelgenerated gases is strongly temperature-dependent, and ranges from CO2(g)-dominated (for temperatures ≤80 °C) to H2O(g)-dominated (and more H2S(g) rich) for temperatures >100 °C.We find that this range ofmodel gas compositions reproduces well the (H2O-CO2-STOT) compositional range of reservoir waters and surface gas emissions in Iceland. From this validation of the model in an extreme end-member environment of high scrubbing,we conclude that EQ3/6-based reaction path simulations ...